Dzieciobójstwo w ujęciu prawnym i kościelnym - Polak, Aleksandra (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2018)
The purpose of this science paper is to show infanticide according to the Polish Penal Code and Code of Canon Law, including the history of this crime. Killing one’s own child is considered as murder privileged in polish law. What is more, infanticide can be committed only by a woman who is under the influence of the delivery or during the period of delivery. Every other person like the father of the child is treated as a responsible for common murder. It also involves everyone who cooperates with a mother of the child. The Code of Canon Law opposes all forms of infanticide, including abortions which is a different crime according to the Polish Penal Code. This article is attempting to define differences between polish penal law and canon law. According to the church doctrine infanticide is always a murder and a sin. By contrast, in secular courts it is not always tried as homicide and it is considered as a privileged crime. What is more, church protects every stage in the development of a human being from the moment of conception. In addition, this article lists applicable penalties, taking into consideration the Code of Canon Law
Keywords: dzieciobójstwo; przestępstwo uprzywilejowane; kodeks karny; kodeks prawa kanonicznego; grzech ciężki